2013
DOI: 10.5935/abc.20130079
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Stiffness is an Independent Predictor of Stroke in Hypertensive Patients

Abstract: Aortic PWV is a risk factor for stroke in hypertensive patients, and its integration into clinical follow-up programs in patients whose cardiovascular risk is manifest is strongly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
1
25
0
2
Order By: Relevance
“…More specifically, we show that this effect is associated with the consumption of 3 g KWG dose, and the effect appeared to not be dose dependent. These findings are of interest given the well-established predictive ability of AI in determining future CVD events [21,22]. Our results also indicate that KWG does not significantly reduce postprandial glycemia relative to control.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…More specifically, we show that this effect is associated with the consumption of 3 g KWG dose, and the effect appeared to not be dose dependent. These findings are of interest given the well-established predictive ability of AI in determining future CVD events [21,22]. Our results also indicate that KWG does not significantly reduce postprandial glycemia relative to control.…”
Section: Discussionsupporting
confidence: 63%
“…Arterial stiffness has emerged as a novel marker of CVD risk, displaying a clear independent predictive value [22,23]. As such, acute improvements in AI demonstrated with 3 g KWG may have a clinical potential, and could aid in broadening our understanding on the hemodynamic potential of ginseng.…”
Section: Discussionmentioning
confidence: 99%
“…This substudy identified that wave reflection index, even when adjusted for age, sex, heart rate, brain natriuretic protein level, fasting glucose, antihypertensive regimen, and carotid intima-media thickness, remained a predictor of future cardiovascular events ( P =0.003) 24. A study by Pereira et al showed that, independent of hypertension and other risk factors for arteriosclerotic heart disease, individuals with aortic stiffness had a 1.39 (95% confidence interval 1.08–1.72; P =0.02) increase in relative risk of fatal stroke 25. Other studies have shown an association between increased aortic stiffness and microvascular cerebral disease, including lacunar infarcts, in individuals with hypertension 26.…”
Section: Clinical Importance Of Aortic Stiffnessmentioning
confidence: 99%
“…Arterial stiffness is an important indicator of cardio-/ cerebrovascular comorbidities (e.g., hypertension, diabetes, and atherosclerosis) (1)(2)(3)(4) and risks (e.g., stroke) (5). It also aids in tracking the progression of other common cardiovascular diseases, such as Marfan syndrome and abdominal aortic aneurysm (AAA) (6,7).…”
Section: Introductionmentioning
confidence: 99%